DOA estimation for different frequency with different angles based on wideband co‐prime array. Issue 21 (7th October 2019) - Wang, Geng; He, Minghao; Tang, Yuwen; Feng, Mingyue; Han, Jun; Fan, Xikun
Abstract : Most of the signals received in the field of wireless communication, radar, and sonar are wideband, so there is an active research on wideband direction‐of‐arrival (DOA). Many approaches of DOA estimation for different frequency with same angles have already been proposed, such as off‐grid sparse learning via iterative minimisation (OGSLIM). Based on the OGSLIM algorithm, this study proposed frequency group decision strategy (FGDS). Based on the different information of the number of signals at different frequency bins, FGDS can obtain the estimation results of DOA at each frequency bin. The results of simulations demonstrate that the proposed algorithm outperforms other reported ones.